The transcription factor FOXM1 regulates the balance between proliferation and aberrant differentiation in head and neck squamous cell carcinoma. Issue 1 (3rd December 2019) - Roh, Vincent; Hiou‐Feige, Agnès; Misetic, Vinko; Rivals, Jean‐Paul; Sponarova, Jana; Teh, Muy‐Teck; Ferreira Lopes, Silvia; Truan, Zinnia; Mermod, Maxime; Monnier, Yan; Hess, Jochen; Tolstonog, Genrich V; et al.
Abstract: Sustained expression of FOXM1 is a hallmark of nearly all human cancers including squamous cell carcinomas of the head and neck (HNSCC). HNSCCs partially preserve the epithelial differentiation program, which recapitulates fetal and adult traits of the tissue of tumor origin but is deregulated by genetic alterations and tumor‐supporting pathways. Using shRNA‐mediated knockdown, we demonstrate a minimal impact of FOXM1 on proliferation and migration of HNSCC cell lines under standard cell culture conditions. However, FOXM1 knockdown in three‐dimensional (3D) culture and xenograft tumor models resulted in reduced proliferation, decreased invasion, and a more differentiated‐like phenotype, indicating a context‐dependent modulation of FOXM1 activity in HNSCC cells. By ectopic overexpression of FOXM1 in HNSCC cell lines, we demonstrate a reduced expression of cutaneous‐type keratin K1 and involucrin as a marker of squamous differentiation, supporting the role of FOXM1 in modulation of aberrant differentiation in HNSCC. Thus, our data provide a strong rationale for targeting FOXM1 in HNSCC. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.